The Latino Museum of History, Art, and Culture Press Conference
TLM Press Conference 02/14/1996 – 1:25: 33 The Latino Museum Opening/Dedication Hector Rodriguez Behind Camera Starts with nametags being made in the TLM Offices 1:02 - Stage with chairs and P.A. system being set up out front of TLM Shots showing individual workers 4:39 – Discussion between Denis Lugo and 4 unknown males in Spanish. (Translation Needed) 7:46 - Shots of National flags being strung up (Spain, Uruguay, Argentina) and P.A. system sound check 9:36 - 2 Women setting up a table for Membership sign-up for TLM 12:30 - Group setting up a string of flags in the background of stage area 17:23 - Flowers are cut and made ready for presentation 19:21 - Camera Crews and People are shown setting up and checking-in for event, School children arrive for event 21:30 - In the back offices of TLM people mingle. The Mayor of Los Angeles shows up and greets people. Andy Garcia is shown plans/model of Museum layout and discusses the space with unknown male. The Mayor takes pictures with Andy Garcia, then the whole group of presenters gets together for group shots. 29:36 - Presenters are led out to stage area. String quartet plays songs in the background (Vivachi Chamber Group) 32:56 - First speaker is Rosanna DeSoto. She introduces Roberto Grand for a quick reflection of his. She then introduces the next speaker…. 34:03 – Sen. Chuck Calderon - President and Chairman of Board 35:21 – Rosanna Desoto brought back 37:49 – Director of the Museum Denise Lugo brought up to speak 39:06 – Andy Garcia introduced and brought up to speak 40:32 – Mayor of Los Angeles introduced Richard J. Riordan. Mentions and thanks Maria Conchita Alonzo, Andy Garcia and Rosanna DeSoto. He donates a piece of art for the first exhibition of TLM. He also asks that this day be Latino Heritage Day. 48:44 – Maria Conchita Alonzo introduced to speak. She mentions that The Latino Museum, via the Bank of America, received a 15 year loan at 1$ a year 49:56 – Head of Bank of America, Donald A Mulane Executive Vice-President of Community Development of Bank of America introduced by Maria Conchita Alonzo. Discusses origins of Bank of America that provided the Loan. Rosanna presented with Key to the Building. 53:41 –Chuck Calderon steps up to the mic to accept Key to the Building and thanks Bank Of America 54:51 – Ms Torres introduced. Her first few sentences are in Spanish (Translation Needed) 55:56 – Childrens Choir introduced and sings 57:30 – Maris Conchita Alonzo is brought back up to introduce the head of the Counsel of Mexico Senor Jose Angeles Pescador 104:12 – Sen. Calderon is called up to recognize and thank members of the City Counsel. He thanks specifically General Manager of the City of Los Angeles Cultural Affairs Dept. Al Lodel? and General Manager of the Community Development Dept. Parker Anderson. He then invites up Rita Walters, Councilman Richard Alatore, Mike Hernandez and Richard Alarcon. 1:07:47 – Rita Walters first to speak 1:09:13 – Unknown Male speaks 1:10:37 – Unknown Male speaks 1:12:49 – Unknown Male speaks 1:15:23 – Congresswoman Lucille Roybal-allard is introduced to speak 1:17:38 – Father Gomez of Our Lady Queen of the Angels introduced for a Blessing of the Museum 1:25:25 – Last thank you by Rosanna DeSoto